2018
DOI: 10.1186/s42234-018-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of renal nerves for modulating urine glucose excretion in rats

Abstract: Background: The role of the kidney in glucose homeostasis has gained global interest. Kidneys are innervated by renal nerves, and renal denervation animal models have shown improved glucose regulation. We hypothesized that stimulation of renal nerves at kilohertz frequencies, which can block propagation of action potentials, would increase urine glucose excretion. Conversely, we hypothesized that low frequency stimulation, which has been shown to increase renal nerve activity, would decrease urine glucose excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
(74 reference statements)
3
9
0
Order By: Relevance
“…Animal studies are often a necessary step to unravel the mechanisms of physiology leading to novel clinical applications in humans (figure 2). Animal experiments could also suggest a new field of BM application, as in the case of metabolic diseases [159,160]. Animal studies are also useful for investigating stimulus-evoked neural activity and the correlation between neural fibre-type activation and the related physiological effect [161,162].…”
Section: Animal Studies Towards Ans Bm Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies are often a necessary step to unravel the mechanisms of physiology leading to novel clinical applications in humans (figure 2). Animal experiments could also suggest a new field of BM application, as in the case of metabolic diseases [159,160]. Animal studies are also useful for investigating stimulus-evoked neural activity and the correlation between neural fibre-type activation and the related physiological effect [161,162].…”
Section: Animal Studies Towards Ans Bm Applicationsmentioning
confidence: 99%
“…Metabolic diseases are also related to the overactivation of the sympathetic nervous system, which leads to hypertension and insulin resistance, preliminary conditions for developing type 2 diabetes [197]. Several studies explored the possibility of suppressing sympathetic tone with stimulation to treat metabolism-related problems, as demonstrated in the case of renal nerve stimulation to control glucose excretion in urine in rats [160] and chronic CSN stimulation to restore insulin sensitivity and glucose tolerance in rats [159].…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…In addition to the vagus nerve, studies on the regulatory role of other peripheral and CNS circuitries and the therapeutic usage of their modulation are considerably adding to progress in bioelectronic medicine ( Fig. 3; Talbot et al 2015;Guduru et al 2018;Güemes and Georgiou 2018;Jiman et al 2018;Kibleur and David 2018;Kovatchev 2018;Zhang et al 2018;Pavlov and Tracey 2019). These studies use methodological advances in material science, bioengineering, neuroscience, data analytics, computer modeling and mathematics, immunology, molecular biology, and other disciplines ( Fig.…”
Section: Bioelectronic Medicine: An Expanding Fieldmentioning
confidence: 99%
“…These findings may be of interest for further systematic investigations of the effects of VNS and its specific physiological effects (Qing et al, 2018). In addition to the vagus nerve, interesting research focusing on clinically-relevant physiological regulation of neural activity of other peripheral nerves was also published (Jiman et al, 2018). Previous findings have indicated that renal denervation has beneficial effects in treating drug-resistant hypertension (Pan et al, 2015).…”
mentioning
confidence: 92%
“…There is also a growing interest in the role of the renal nerves in the regulation of glucose homeostasis (Pan et al, 2015). Using a cuff electrode positioned to modulate renal nerves residing adjacent to the left renal artery, Jiman et al (Jiman et al, 2018) reported that stimulation at kilohertz frequencies (1-50 kHz), designed to block action potential propagation, or low frequencies (2-5 Hz), with intravenous administration of a glucose, increased, or respectively lowered, urine glucose excretion (Jiman et al, 2018). This is an interesting avenue for organ-targeted neuromodulation studies aimed at altering glucose excretion for therapeutic benefit.…”
mentioning
confidence: 99%